WOMAN AND TECHNOLOGY: A STUDY ON GENDER PORTRAYAL OF A FEMALE CYBORG IN GHOST IN THE SHELL (2017) MOVIE - Pujo Sakti Nur Cahyo; Riyan Evrilia Suryaningtyas (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2020)
This study aims to analyze gender portrayal in Ghost in the Shell (2017) movie by applying Donna Haraway’s concept of cyborgs as in her Cyborg Manifesto. Focusing on the analysis of narrative and non-narrative elements, this research seeks to reveal how the main character is portrayed as a female cyborg. As a result, the writers found that her shifting existence as a female cyborg in the movie is the representation of how women can be the subject by affiliating with technology. The assumption of women as the